Analysis of the Batik Tutur Motif on 'Justin Holiday' Clothing. - Fauzan, Muhammad (Institut Seni Indonesia Padang Panjang, 2024)
Unearthing the original Blitar batik is not an easy task. The existence of this batik was first discovered through black-and-white photos found in old Dutch colonial archives, where it was written: